The Effects of Occupational Modality Therapy on the Independence Level of the Elderly - Apriani, Miftah; Wulandari, Ria (Universitas Ahmad Dahlan, 2021)
Background: Independence in elderlies is the ability to carry out daily activities. The Activity of Daily Living (ADL) is a form of measuring a person's ability to perform ADL independently so that information on elderly morbidity can be analyzed. Occupational therapy is the art and science of supporting interactions in everyday life through work (occupation) that enables people to do work that promotes health and well-being and enables a just and inclusive society, encouraging everyone to optimize their potential in the workplace from everyday life. This study aims to identify the independence level of elderlies before and after occupational modality therapy. Methods: The method employed in this study was a quasi-experimental technique design using a pretest-posttest control group design. Results: The results of the study showed a p-value of 0.00, indicating that occupational modality therapy affected the level of independence of the elderlies who were given treatment with a change of independence level from 13.50 to 16.95. Meanwhile, in the control group where the respondents were not given occupational modality therapy, there was no significant difference before and after the final observation. Conclusion: The elderlies who were given treatment became more independent in carrying out their daily activities compared to those who were not given treatment in the control group.